Wiley Encyclopedia of Operations Research and Management Science 2011
DOI: 10.1002/9780470400531.eorms0687
|View full text |Cite
|
Sign up to set email alerts
|

Prospect Theory

Abstract: Prospect theory is a descriptive theory of how individuals choose among risky alternatives. The theory challenged the conventional wisdom that economic decision makers are rational expected utility maximizers. We present a number of empirical demonstrations that are inconsistent with the classical theory, expected utility, but can be explained by prospect theory. We then discuss the prospect theory model, including the value function and the probability weighting function. We conclude by highlighting several a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…This principle also applies to probability assessments. Chiu and Wu (2010) make the fairly intuitive observation (backed by empirical evidence) that increasing one's chances of winning a prize from, say, 0% to 1% or 5% to 6%, each seem more consequential than increasing one's chances from 36% to 37%; and, among the former two, 0% to 1% seems particularly consequential (we return to this below).…”
Section: Diminishing Sensitivity and Diminishing Marginal Benefitsmentioning
confidence: 92%
“…This principle also applies to probability assessments. Chiu and Wu (2010) make the fairly intuitive observation (backed by empirical evidence) that increasing one's chances of winning a prize from, say, 0% to 1% or 5% to 6%, each seem more consequential than increasing one's chances from 36% to 37%; and, among the former two, 0% to 1% seems particularly consequential (we return to this below).…”
Section: Diminishing Sensitivity and Diminishing Marginal Benefitsmentioning
confidence: 92%
“…PT has found application in various domains, such as mental accounting in behavioral economics and modeling driver compliance or route choice in transportation ( 46 ). PT was introduced by Kahneman and Tversky, who observed that risk decisions are often influenced by subjective considerations that, in turn, may have been shaped by language expressions, leading to different preferences in different scenarios ( 47 ).…”
Section: Methods and Datamentioning
confidence: 99%
“…One fundamental concept of Loss aversion, a concept within prospect theory, describes the inclination of individuals to prioritize avoiding losses more than gaining equivalent gains. Losing has a more significant psychological impact than winning, potentially leading to risk-averse behavior (Chiu, A., & Wu, G. (2018).…”
Section: Prospect Theory's Fundamental Ideas and Tenets Includementioning
confidence: 99%